2004
DOI: 10.1038/sj.bmt.1704637
|View full text |Cite
|
Sign up to set email alerts
|

High-dose CEB vs BEAM with autologous stem cell transplant in lymphoma

Abstract: , 72 patients with non-Hodgkin's lymphoma or Hodgkin's disease underwent high-dose chemotherapy with autologous stem cell transplant conditioned with either cyclophosphamide, etoposide, carmustine (CEB) or carmustine, etoposide, cytarabine, melphalan (BEAM) at a single institution. In all, 52 patients received CEB and 20 patients received the BEAM regimen. Patient characteristics that were significantly different between the two groups are tumor grade and extranodal involvement (P ¼ 0.0196, 0.0341, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 17 publications
(42 reference statements)
2
26
1
3
Order By: Relevance
“…35 The association of idarubicin with busulfan for autologous SCT in AML patients caused profound mucosal derangement in 82% of patients. 36 High doses of melphalan (200 mg/m 2 ), given prior to autologous SCT for multiple myeloma, caused mucosal injury in about 35% of them; 37 intermediate doses (100 mg/m 2 ) significantly reduced the incidence of mucositis to 23%, as reported in a study including patients over 70 years old.…”
Section: Mucositis During Transplantationmentioning
confidence: 99%
“…35 The association of idarubicin with busulfan for autologous SCT in AML patients caused profound mucosal derangement in 82% of patients. 36 High doses of melphalan (200 mg/m 2 ), given prior to autologous SCT for multiple myeloma, caused mucosal injury in about 35% of them; 37 intermediate doses (100 mg/m 2 ) significantly reduced the incidence of mucositis to 23%, as reported in a study including patients over 70 years old.…”
Section: Mucositis During Transplantationmentioning
confidence: 99%
“…21 The severity of OM is closely correlated with the conditioning regimen, 22 and has been reported to be as high as 75% in lymphoma patients conditioned with carmustine, etoposide, cytarabine and melphalan regimen. 23 The association of idarubicin with BU for autologous HSCT in patients with AML caused profound mucosal derangement and pain in 82% of patients. 24 In myeloma patients, a high dose (200 mg/m 2 ) of melphalan is associated with a 30-35% incidence of OM.…”
Section: Epidemiology and Causal Factors Of Specific Pain Syndromes Imentioning
confidence: 99%
“…Randomized trials are lacking. In adult studies, 5-year OS is reported at 40-55 % for both regimens, although BEAM has been reported to have a more favorable toxicity profi le than CVB, including less hepatotoxicity, mucositis, and treatment-related mortality (Wang et al 2004 ;Puig et al 2006 ). Attempts to intensify CVB chemotherapy with infusional etoposide and dose escalation of BCNU were associated with improved response rates but a high rate of interstitial pneumonitis (Benekli et al 2008 ).…”
Section: Conditioning Regimens For Autologous Hctmentioning
confidence: 98%